Kemandirian Lokal: Upaya Pemberdayaan Hak-hak Sipil - Purwo Santoso (Jurnal Ilmu Sosial dan Ilmu Politik, 1999)
The term local self-reliance is chosen to incorporate the three concepts widely discussed on local politics in Indonesia: local autonomy, federalism and separatist movement. This article offers a critical assessment on the discourse on the issues by showing various blunders in interpreting am! then implement key political concept, such as the strength of the state, state-society relationship, and the relationship of local-central agencies. These blunders are rooted from the preoccupation of the instrumentality of the state. Aware of those blunders, this article suggests to analyse the issue from the framework of political movement.